Leadership Dynamics in Scrum Teams : Navigating Agile Transformations in Knowledge-Intensive Environments - Shahriari, Nassim (2025)
Agile methodologies, and Scrum in particular, have changed how software teams organize work and leadership. This thesis explores how leadership is practiced within Scrum teams and how it changes during Agile transformation. The study is guided by two research questions focusing on leadership characteristics in Scrum teams and leadership evolution during transformation. A qualitative research approach was applied using semi-structured interviews with ten participants, including Scrum Masters, Product Owners, Developers, Agile Coaches, and one academic supervisor. The data were analyzed through thematic analysis. The findings show that leadership in Scrum teams is distributed and situational, and strongly influenced by psychological safety and role clarity. The Scrum Master plays an important enabling role, while leadership also emerges from other team members based on expertise and context. During Agile transformation, leadership shifts from command-and-control toward enabling behaviors, although this change is often constrained by organizational structures and cultural resistance. The study contributes to a better understanding of Agile leadership by highlighting the gap between Scrum theory and real-world practice.